Housing situation and healthcare for patients in a psychiatric centre in Berlin, Germany: a cross-sectional patient survey. Issue 12 (29th December 2019) - Schreiter, Stefanie; Heidrich, Sascha; Zulauf, Jamie; Saathoff, Ute; Brückner, Anne; Majic, Tomislav; Rössler, Wulf; Schouler-Ocak, Meryam; Krausz, Michael R; Bermpohl, Felix; Bäuml, Josef; Gutwinski, Stefan
Abstract : Objective: To determine the housing situation among people seeking psychiatric treatment in relation to morbidity and service utilisation. Design: Cross-sectional patient survey. Setting: Psychiatric centre with a defined catchment area in Berlin, Germany, March–September 2016. Participants: 540 psychiatric inpatients including day clinics (43.2% of all admitted patients in the study period (n=1251)). Main outcome measures: Housing status 30 days prior the interview as well as influencing variables including service use, psychiatric morbidity and sociodemographic variables. Results: In our survey, 327 participants (68.7%) currently rented or owned an own apartment; 62 (13.0%) reported to be homeless (living on the street or in shelters for homeless or refugees); 87 (18.3%) were accommodated in sociotherapeutic facilities. Participants without an own apartment were more likely to be male and younger and to have a lower level of education. Homeless participants were diagnosed with a substance use disorder significantly more often (74.2%). Psychotic disorders were the highest among homeless participants (29.0%). Concerning service use, we did neither find a lower utilisation of ambulatory services nor a higher utilisation of hospital-based care among homeless participants. Conclusions: Our findings underline the need for effective housing for people with mental illness. Despite many sociotherapeutic facilities, a concerning number of people with mental illness is living in homelessness. Especially early interventions addressing substance use might prevent future homelessness.